2016
DOI: 10.4244/eijy15m11_11
|View full text |Cite
|
Sign up to set email alerts
|

Regular drug-eluting stents versus the dedicated coronary bifurcation sirolimus-eluting BiOSS LIM® stent: the randomised, multicentre, open-label, controlled POLBOS II trial

Abstract: MACE rates as well as TLR rates were comparable between the BiOSS LIM and rDES. At 12 months, cumulative MACE incidence was similar in both groups (11.8% vs. 15%), as was the TLR rate (9.8% vs. 9%). Significantly lower rates of restenosis were observed in the FKBI subgroup of the BiOSS group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
0
30
0
6
Order By: Relevance
“…It achieved acceptable results both in in vivo studies and in clinical trials. However, clinical results of BiOSS Expert and BiOSS LIM were not very different that was caused mainly by high late lumen loss values in case of BiOSS LIM . Therefore, the idea to reduce the late lumen loss and as a result TLR rate using thinner struts appeared…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It achieved acceptable results both in in vivo studies and in clinical trials. However, clinical results of BiOSS Expert and BiOSS LIM were not very different that was caused mainly by high late lumen loss values in case of BiOSS LIM . Therefore, the idea to reduce the late lumen loss and as a result TLR rate using thinner struts appeared…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the optimal approach for true coronary bifurcations is still a subject of discussion, especially when the side branch is large, narrowed by a long plaque or not simply accessible . The role of dedicated devices in this setting remains unclear compared to the provisional approach as shown in the Tryton IDE study or POLBOS I and II trials …”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis incorporating the results of 9 RCTs including 2,569 patients reported that a two‐stent strategy had similar clinical safety (cardiac death and stent thrombosis) and efficacy (TLR, target vessel revascularization) compared with the PS strategy. Moreover, studies evaluating the performance of dedicated bifurcation devices, such as the BiOSS LIM stent also showed similar clinical outcomes in comparison to PS approach …”
Section: Discussionmentioning
confidence: 87%
“…No randomised study has given results for this type of stent compared to regular DESs. A BIOSS Lim stent is a dedicated device demonstrating clinical efficacy in a recently published randomised POLBOS II trial [53]. At 12 months, the cumulative MACE incidence was similar in both groups (11.8% [BiOSS] vs. 15%…”
Section: General Conclusion and Future Directionsmentioning
confidence: 99%